The Food Crisis and Food Security: Towards a New World Food Order? - Christophe Golay (Revue Internationale de Politique de Développement)
The worst food crisis since 1974 broke out in 2007-08. Higher world market prices of food commodities (especially wheat, rice, soya and maize) sparked an unprecedented increase in the number of hungry people. Despite moderately lower prices since the summer of 2008, the number of the hungry continued to rise in 2009. This food crisis has placed the fight against hunger on the international agenda. Since March 2008 governments UN agencies and many social movements have adopted positions on the causes of the crisis and the means to address it. Unfortunately, while these parties are trying to coordinate their activities and suggest new approaches, the old recipes for producing more food are often brought up. Contradictory proposals are made and the thought given to the causes underlying hunger and the food crisis (social, economic and political discrimination and exclusion) has gone largely unheeded. The first Millennium Development Goal, which calls for cutting the percentage of hungry people by half by 2015, is clearly out of reach. But the food crisis might lead to a new world food order based on the three pillars of food assistance, food security and the right to food.